Ascorbate status and fibrinogen concentrations after cerebrovascular accident. Issue 2 (February 1982) - Hume, R; Vallance, B D; Muir, M M
Abstract : Leucocyte ascorbate (LA) and serum ascorbate (SA) were measured in patients who had sustained an acute cerebrovascular accident. There was a significant fall in LA and Sa within 24 hours of the incident and this persisted for several weeks. The "stress" of the event resulted in a rise in serum cortisol concentration and depletion of both pituitary and adrenal glands of ascorbate when examined at post mortem. Serum fibrinogen concentrations also rose above normal. The role of ascorbate in pituitary and adrenal function and the relation of ascorbate to acute and chronic vascular disorders has still to be established.